2006
DOI: 10.1128/aac.00761-05
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic In Vitro Antiretroviral Activity of a Humanized Monoclonal Anti-CD4 Antibody (TNX-355) and Enfuvirtide (T-20)

Abstract: Recently, antiretroviral agents directed at several steps involved in viral entry have been shown to reduce viral replication in vitro and in vivo. We have demonstrated a high level of in vitro synergistic antiretroviral activity for two entry inhibitors that are directed at sequential steps in the entry process.Combination chemotherapy has had a profound effect on human immunodeficiency virus type 1 (HIV-1)-associated morbidity and mortality (8). Although there are now more than 20 approved antiretroviral che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…MOI, multiplicity of infection. Previous studies using the HIV-1 inhibitors continuously present in peripheral blood mononuclear cell (PBMC) cultures against infection with ‡ SHIV-162P3 virus (Veazey et al, 2003); § Ba-L virus (Maeda et al, 2004); ¶ HIV IIIB virus (Zhang et al, 2006); # Ba-L virus (Van Herrewege et al, 2002); EC 50 , 50% effective compound concentration; MOI, multiplicity of infection; NF, not found. be used after a possible risk exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOI, multiplicity of infection. Previous studies using the HIV-1 inhibitors continuously present in peripheral blood mononuclear cell (PBMC) cultures against infection with ‡ SHIV-162P3 virus (Veazey et al, 2003); § Ba-L virus (Maeda et al, 2004); ¶ HIV IIIB virus (Zhang et al, 2006); # Ba-L virus (Van Herrewege et al, 2002); EC 50 , 50% effective compound concentration; MOI, multiplicity of infection; NF, not found. be used after a possible risk exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this class of compounds was previously shown to prevent cell-free virus infection in cervical tissue (Hu et al, 2004) and macaques (Veazey et al, 2003a(Veazey et al, , 2003b(Veazey et al, , 2005 and some binding inhibitors were active against cell-associated virus at high concentrations (Lu et al, 2006). Therefore, although binding/fusion inhibitors alone may be insufficient as single microbicides, they could make a valuable contribution to a combination microbicide strategy to protect non-infected target cells (Liu et al, 2005;Veazey et al, 2005;Sterjovski et al, 2006;Zhang et al, 2006).…”
mentioning
confidence: 99%
“…Consistent with the observed lack of cross-resistance, critical determinants of maraviroc and enfuvirtide resistance have been mapped to the V3 region and gp41, respectively, and do not appear to overlap with the determinants of ibalizumab resistance reported in this study. In vitro drug combination studies have demonstrated synergistic antiviral activities for ibalizumab and enfuvirtide (44) and additive-to-synergistic activity for ibalizumab and maraviroc (S. P. Weinheimer et al, unpublished data), providing further support for ibalizumab as a potentially valuable addition to antiretroviral drug regimens. However, more stud- 6.…”
Section: Vol 85 2011mentioning
confidence: 99%
“…Ibalizumab (formerly known as TNX-355) is a humanized IgG4 monoclonal antibody that blocks HIV-1 entry by binding to human CD4 (8,12,14,33). It was engineered from its mouse progenitor (5A8) by grafting the mouse complementary-determining region (CDR) onto a human IgG4 construct (4,5).…”
mentioning
confidence: 99%